Outcomes of single versus double hormone receptor–positive breast cancer. A GEICAM/9906 sub-study. (May 2018) - Ethier, J.L.; Ocaña, A.; Rodríguez Lescure, A.; Ruíz, A.; Alba, E.; Calvo, L.; Ruíz-Borrego, M.; Santaballa, A.; Rodríguez, C.A.; Crespo, C.; Ramos, M.; Gracia Marco, J.; et al.
Abstract: Background: Retrospective data suggest better outcomes for patients with double hormonal receptor (oestrogen [ER] and progesterone receptor [PgR])–positive (dHR+) early breast cancer, compared with single hormonal receptor–positive, sHR+, (ER+/PgR– or ER–/PgR+) disease. Here, we evaluate the classification according to intrinsic subtypes and clinical outcomes of sHR+ versus dHR+ in HER2-negative breast cancer patients enrolled in GEICAM/9906 study (NCT00129922 ). Methods: Archival tumours were retrieved retrospectively for the analysis of ER, PgR and HER2 status and classified into intrinsic subtypes using the PAM50 gene expression assay. Disease-free survival (DFS) and overall survival (OS) were explored using a Cox proportional hazard analysis. Results: Data on intrinsic subtypes were available in 571 (50%) patients with ER+ and/or PR+, and HER2-negative primary tumours. The incidence of luminal A and luminal B subtypes were 52%/36% in dHR+ tumours (ER+/PgR+), and 15%/58% in ER+/PgR–tumours. ER–/PgR+ tumours were mainly luminal A (52%). Compared with ER+/PgR+ patients, DFS was similar in ER–/PgR+ (hazard ratio [HR] 1.15, 95% confidence interval [CI] 0.57–2.34, p = 0.70) but worse in ER+/PgR– patients (HR 1.60, 95% CI 1.12–2.28, p < 0.01). Similar results were observed for OS (HR 1.50, p = 0.30 and HR 1.86, p < 0.01, respectively). Conclusions: The ER+/PgR– group is characterised by higher proliferation and worse outcomes. In spite of the ER–/PgR+ subgroup resembles ER+/PgR+ disease in terms of molecular subtypes and outcomes, the small number of patients in this subgroup prevents from drawing any conclusions. Trial registration: EudraCT: 2005-003108-12 (retrospectively registered 28/06/2005). Clinicaltrials.gov Identifier: NCT00129922 (retrospectively registered 10/08/2005). Highlights: Oestrogen and progesterone receptor (ER+/PgR)–breast cancers are mainly luminal B or HER-2 enriched. The luminal A subtype is predominant in ER+/PgR+ and ER–/PgR+ breast cancers. Absence of PgR expression provided higher risk of recurrence and decreased survival.